Analysis of Elliptic Curve Cryptography (ECC) for Energy Efficiency in Wireless Sensor Networks - Zain Ul Abideen Tariq; Shahzad Shahid Peracha; Khurram Aziz (NUST Journal of Engineering Sciences, 2009)
Rapid growth of wireless sensor networks (WSN) in recent times has resulted in greater security requirements. One of the primary concerns in wireless sensor networks is energy efficiency and security mechanisms are no different.  Currently, security in wireless sensor networks is often implemented by symmetric key cryptography due to its low-power implementation. Public Key Cryptography (PKC), on the other hand, is advantageous as it requires less overhead information during transmission of packets that ultimately lessens overall size of the protocol. In addition, Public Key Cryptography provides better data confidentiality and authentication in wireless sensor networks. In this study, we focus on Public Key Cryptography for greater efficiency in key distribution, low protocol overhead and efficient hardware implementation on the sensor nodes. Considering the constraints of energy efficient wireless sensor networks, we analyze and compare some well known Public Key algorithms, their implementation in wireless sensor networks, and how these algorithms can benefit the fundamental security services. We also evaluate energy consumption parameters for encryption as well as data transmission and suggest energy efficient encryption mechanisms.